2017
DOI: 10.1098/rspb.2017.1089
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to public goods cheats in Pseudomonas aeruginosa

Abstract: Cooperation in nature is ubiquitous, but is susceptible to social cheats who pay little or no cost of cooperation yet reap the benefits. The effect such cheats have on reducing population productivity suggests that there is selection for cooperators to mitigate the adverse effects of cheats. While mechanisms have been elucidated for scenarios involving a direct association between producer and cooperative product, it is less clear how cooperators may suppress cheating in an anonymous public goods scenario, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 59 publications
1
46
2
Order By: Relevance
“…; O'Brien et al. ). However, despite the great advance these insights provide for our understanding of microbial social interactions and community dynamics, most of the work carried out so far stems from one type of siderophore (pyoverdine) produced by one type of bacterium (fluorescent pseudomonads, particularly Pseudomonas aeruginosa ), but also see Cordero et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…; O'Brien et al. ). However, despite the great advance these insights provide for our understanding of microbial social interactions and community dynamics, most of the work carried out so far stems from one type of siderophore (pyoverdine) produced by one type of bacterium (fluorescent pseudomonads, particularly Pseudomonas aeruginosa ), but also see Cordero et al.…”
mentioning
confidence: 99%
“…The key question in this context is how cooperative siderophore secretion can be evolutionarily maintained, given that siderophore-negative cheater mutants can arise and freeride on the public goods produced by others (West et al 2006;Özkaya et al 2017). A large body of work has tackled this question and revealed that cheating and cheater control are major determinants of bacterial population dynamics in host infections, in laboratory experiments, and in environmental communities (Cordero et al 2012;Andersen et al 2015;Kümmerli et al 2015;Bruce et al 2017;Butaitė et al 2017;O'Brien et al 2017). However, despite the great advance these insights provide for our understanding of microbial social interactions and community dynamics, most of the work carried out so far stems from one type of siderophore (pyoverdine) produced by one type of bacterium (fluorescent pseudomonads, particularly Pseudomonas aeruginosa), but also see Cordero et al (2012), Kümmerli et al (2014), and Scholz and Greenberg (2015) for exceptions.…”
mentioning
confidence: 99%
“…We were further interested if such social cheating could leave a phenotypic or genetic fingerprint in the population of the wild type B. subtilis. Previous studies have shown that cooperators can adapt to presence of cheats for example by decreasing the amount of released public goods and therefore minimizing cheating opportunities [2,14,15]. As B. subtilis exhibits phenotypic heterogeneity in eps matrix gene expression [39,40] ( Supplementary Fig.…”
Section: 'Hyper On' Matrix Producers Emerge During Evolution With Cheatsmentioning
confidence: 99%
“…Cooperative interactions are prevalent for all life forms [1], even for simple microbes that often exist in communities of matrix bound surface-attached cells called biofilms [2][3][4][5][6]. However, when costly products such as siderophores [7,8], extracellular polymeric substances [9,10], digestive enzymes [11], and signaling molecules [12,13] are secreted and shared, cooperative behavior 3 becomes susceptible to cheating [2,[14][15][16], where mutants defective in cooperation can still benefit from cooperative community members [4,5,17]. It has been shown that spatially structured biofilms, where interactions with clonemates are common and diffusion of public goods is limited, may serve as natural defense against cheating [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation